2008
DOI: 10.3324/haematol.11287
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 pilot study of pegfilgrastim and filgrastim for mobilizing peripheral blood progenitor cells in patients with non-Hodgkin's lymphoma receiving chemotherapy

Abstract: BackgroundGrowth factors are frequently used to aid peripheral blood progenitor cell mobilization from bone marrow. This phase 2 study examined the efficacy and safety of pegfilgrastim for mobilizing peripheral blood progenitors cells for autologous transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…In this study, 24 of 25 patients achieved a target CD34 þ cell dose of 2.0 Â 10 6 /kg in a single apheresis procedure. Mobilization with both filgrastim and pegfilgrastim 6 or 12 mg has also been reported by Russell et al 21 following ifosfamide, carboplatin and etoposide chemotherapy. What remains unclear is whether the 14-day interval between the first and second mobilization attempts was insufficient to allow haematopoietic potential to have been restored.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, 24 of 25 patients achieved a target CD34 þ cell dose of 2.0 Â 10 6 /kg in a single apheresis procedure. Mobilization with both filgrastim and pegfilgrastim 6 or 12 mg has also been reported by Russell et al 21 following ifosfamide, carboplatin and etoposide chemotherapy. What remains unclear is whether the 14-day interval between the first and second mobilization attempts was insufficient to allow haematopoietic potential to have been restored.…”
Section: Discussionmentioning
confidence: 80%
“…In healthy volunteers and donors, in contrast to postchemotherapy mobilization, 12 pegfilgrastim efficacy is strongly dose-dependent in terms of CD34 þ cell mobilization. 5,21 In patients with malignancy, the drawback to increasing the dose of pegfilgrastim is that it leads to sustained BM stimulation, which could delay chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As far as pegfilgrastim is concerned, after chemotherapy the dose of 100 mg/kg has been proposed on the basis of several studies showing that a dose of 100 mg/kg of pegfilgrastim is comparable to a daily administration of 5 mg/kg filgrastim in terms of neutrophil recovery. 12 Hence, in the steady state, there is a rationale for increasing this dose in order to target stem cell mobilization. In healthy volunteers, pharmacokinetic studies have shown that the dose of 300 mg/kg is well tolerated and more efficient than 100 mg/kg for CD34 þ cell mobilization.…”
Section: Mobilization and Collection Regimensmentioning
confidence: 99%
“…This finding is consistent with the results of a recently published, blinded, placebo-controlled multicentre study conducted in patients with malignant lymphoma. 20 These results can be explained by the observation that a single in vivo injection of 6 mg pegfilgrastim in neutropenic patients with multiple myeloma results in plasma concentrations of B100 ng/ml, which are maintained until the time of regeneration of the neutrophilic granulocytes. 21 The levels are thus about 1-log factor higher than those achieved after administration of conventional doses of non-pegylated G-CSF, which, in turn, are 2-log factors higher than the endogenous levels of G-CSF in neutropenic patients.…”
Section: Introductionmentioning
confidence: 98%